2021
DOI: 10.1186/s40168-021-01112-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal(loid) speciation and transformation by aerobic methanotrophs

Abstract: Manufacturing and resource industries are the key drivers for economic growth with a huge environmental cost (e.g. discharge of industrial effluents and post-mining substrates). Pollutants from waste streams, either organic or inorganic (e.g. heavy metals), are prone to interact with their physical environment that not only affects the ecosystem health but also the livelihood of local communities. Unlike organic pollutants, heavy metals or trace metals (e.g. chromium, mercury) are non-biodegradable, bioaccumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 156 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…Cd is very toxic and probably carcinogenic at low concentrations because of its very long half-life (Xu et al, 2020). Hg is a global health threat and causes impairments in the human nervous system (Karthikeyan et al, 2021). Many terrible diseases such as Minamata and Parkinson's disease are related to the overexposure and excessive accumulation of mercury (Cai and Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Cd is very toxic and probably carcinogenic at low concentrations because of its very long half-life (Xu et al, 2020). Hg is a global health threat and causes impairments in the human nervous system (Karthikeyan et al, 2021). Many terrible diseases such as Minamata and Parkinson's disease are related to the overexposure and excessive accumulation of mercury (Cai and Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In methanotrophs, the uptake and utilization of Zn 2+ is a complex process that involves the action of transporters and regulatory proteins. Zn 2+ uptake could be dependent on a similar transport system to Mb …”
Section: Resultsmentioning
confidence: 99%
“…Unlike the BSC in previous studies [ 7 , 8 ], the BAC investigated in this study showed the characteristics of a sponge-like porous structure and the functions of metal(loid) immobilization in aquatic habitats. The BAC has a potential to improve the quality of metal(loid)-contaminated water bodies and has, therefore, been considered a suitable candidate for investigations of microbial interactions with minerals and metal(loid)s derived from mining activities [ 1 , 9 , 10 ]. However, our understanding of metal(loid) bioavailability and microbial communities in BAC of polymetallic water bodies remains limited.…”
Section: Introductionmentioning
confidence: 99%